2016
DOI: 10.1016/j.jarmac.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

How common are WM deficits in children with difficulties in reading and mathematics?

Abstract: HighlightsChildren's learning abilities were associated with WM.The link with verbal WM was stronger for reading than mathematics.The majority of children with learning difficulties had WM deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 78 publications
(124 reference statements)
3
58
0
6
Order By: Relevance
“…Working memory is an important predictor of key developmental outcomes, is fundamental to learning, and predicts academic attainment (Alloway & Alloway, ; Alloway, Gathercole, Kirkwood, & Elliott, ; Cragg & Gilmore, ; Gathercole, Pickering, Knight, & Stegmann, ; Monette, Bigras, & Guay, ). In order to complete classroom learning activities, children must encode, retain, and manipulate information (Baddeley, ; Gathercole & Baddeley, ; Gathercole et al, , ). Therefore, children with poor working memory perform less well on measures of numeracy and literacy (Alloway et al, ; Gathercole et al, ; Holmes et al, ), and this link continues into secondary education (Gathercole & Alloway, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working memory is an important predictor of key developmental outcomes, is fundamental to learning, and predicts academic attainment (Alloway & Alloway, ; Alloway, Gathercole, Kirkwood, & Elliott, ; Cragg & Gilmore, ; Gathercole, Pickering, Knight, & Stegmann, ; Monette, Bigras, & Guay, ). In order to complete classroom learning activities, children must encode, retain, and manipulate information (Baddeley, ; Gathercole & Baddeley, ; Gathercole et al, , ). Therefore, children with poor working memory perform less well on measures of numeracy and literacy (Alloway et al, ; Gathercole et al, ; Holmes et al, ), and this link continues into secondary education (Gathercole & Alloway, ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to complete classroom learning activities, children must encode, retain, and manipulate information (Baddeley, ; Gathercole & Baddeley, ; Gathercole et al, , ). Therefore, children with poor working memory perform less well on measures of numeracy and literacy (Alloway et al, ; Gathercole et al, ; Holmes et al, ), and this link continues into secondary education (Gathercole & Alloway, ).…”
Section: Introductionmentioning
confidence: 99%
“…So, a reasonable prediction is that our large sample of struggling learners will include subgroups of children with either phonological problems or spatial short‐term/working memory difficulties, and that these children will predominantly struggle with reading or maths respectively. Below average nonverbal reasoning is common among individuals with reading (Duranovic, Tinjak, & Turbic‐Hadzagic, ; Gathercole et al., ; Pointus, ; Winner et al., ) and maths problems (Gathercole et al., ; Swanson & Beebe‐Frankenberger, ; Fuchs et al., 2005, , Cirino et al, ), as well as those with ADHD (Holmes et al., 2013). So, another reasonable prediction is that our sample of struggling learners will include a subgroup of children with low fluid reasoning skills, and this will be associated with problems in both reading and maths.…”
Section: Introductionmentioning
confidence: 99%
“…From a cognitive perspective, LRLM could be driven by: (a) domain-specific problems, separately affecting reading and mathematics-specific functions, which are expressed additively in children with LRLM, (b) domain-general problems, in which difficulties in reading and math are secondary to difficulties in general cognitive skills, such as memory, necessary for both domains (Gathercole et al, 2016; Mammarella et al, 2017; Szűcs, 2016; Wang & Gathercole, 2013), or (c) a combination of domain-specific and domain-general problems. Results from behavioral studies have not conclusively identified the contributions of domain-specific and general problems to LRLM.…”
Section: Introductionmentioning
confidence: 99%